Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/1423-0127-19-60
|View full text |Cite
|
Sign up to set email alerts
|

Natural diterpenes from coffee, cafestol and kahweol induce apoptosis through regulation of specificity protein 1 expression in human malignant pleural mesothelioma

Abstract: BackgroundMalignant pleural mesothelioma (MPM) is a highly aggressive cancer with a very poor prognosis. Several clinical studies such as immunotherapy, gene therapy and molecular targeting agents have been tried for treatment of malignant mesothelioma, however, there is no application for effective clinical treatment. Coffee has various biological functions such as anti-oxidant, anti-inflammatory, anti-mutagenic and anti-carcinogenic activities. The therapeutic activities of the bioactive compounds in coffee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 36 publications
(46 reference statements)
0
42
0
Order By: Relevance
“…On the other hand, Mith can affect downstream targets such as Mcl-1 by displacing Sp1 transcription factor from its binding sites on the promoters of oncogenes to inhibit their expression. (16,31) Studies in this laboratory also previously demonstrated that Mith inhibits Mcl-1 protein to exhibit potent anti-tumorigenic activity in rodent models for prostate and oral cancers. (15,32) …”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, Mith can affect downstream targets such as Mcl-1 by displacing Sp1 transcription factor from its binding sites on the promoters of oncogenes to inhibit their expression. (16,31) Studies in this laboratory also previously demonstrated that Mith inhibits Mcl-1 protein to exhibit potent anti-tumorigenic activity in rodent models for prostate and oral cancers. (15,32) …”
Section: Discussionmentioning
confidence: 91%
“…These compounds and coffee drinking are positively correlated with higher level of serum cholesterol lipids, especially in patients with hyperlipidemia [81,82]. Latest research showed that they reduce the risk of colorectal cancer [83].…”
Section: Determination Of Diterpenesmentioning
confidence: 99%
“…Wang et al also suggested an inhibitory effect by 5 mg of caffeine via cAMP/PKA/CREB signal suppression pathway through A 2A receptors treated for 8 weeks in male Sprague‐Dawley rats. Similarly, 30 µM of cafestol has also been noted to inhibit expression of Mcl‐1 and Sp1 protein (9 and 48 h of incubation, respectively) that affect the expression of cyclin D1 and survivin in mesothelioma cells .…”
Section: Anticancer Activitiesmentioning
confidence: 92%
“…In another study, Miglior et al [58] reported a reduction in apoptosis at 1 μM of caffeic acid in human umbilical vein endothelial cells. Similarly, cafestol has also been noted to cause apoptosis by cleavages of the Bid and caspase-3 in mesothelioma cells [38]. It has been also suggested to reduce apoptotic cell death and clonogenic survival in SCC25, CAL27, and FaDu cell lines [59].…”
Section: Effects On Apoptosismentioning
confidence: 97%